Comparison Of Potato (Solanum tuerosum L) and Corn (Zea mays) as Alternative Media To Nutrient Agar Media In The Groth of Staphylococcus aureus Bacteria - Rahmawati; Sa’adah Siregar; Vincentia Ade Rizky (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Microbiology is the study of microorganisms, which are microscopic organisms that can only be observed through a microscope. These microorganisms have an important role in various aspects of life, including in the health sector. Objective: This study aims to evaluate whether alternative media, such as potato and corn, can be used as a substitute for Nutrient Agar in supporting the growth of Staphylococcus aureus bacteria. Methods: This research is experimental, by comparing the effectiveness of potato and corn media as an alternative to Nutrient Agar for the growth of Staphylococcus aureus. Results: The results of the research in the One-way Anova test obtained a significant value (0.00) which means (p <0.05), so it can be concluded that there is a significant difference between the ability of Nutrient Agar media, potato media and corn media in growing Staphylococcus aureus bacteria. To find out each group that has a significant difference, the Post-hoc follow-up test is carried out. The results of the post-hoc follow-up test shown in Figure 4.2.2 obtained a significant value between Nutrient Agar media and potato media (0.00), Nutrient Agar media with corn media (0.558), and between potato and corn media (0.00). Conclusion: The results showed that potato media was significantly different in its ability to grow Staphylococcus aureus compared to Nutrient Agar and corn. Potato media shows potential as an alternative to Nutrient Agar, despite its different effectiveness.